The relationship between sarcopenia and oral sarcopenia in elderly people. (6th March 2020) - Kobuchi, Ryuichiro; Okuno, Kentaro; Kusunoki, Takayuki; Inoue, Taro; Takahashi, Kazuya
Abstract: Background: Sarcopenia in the oral region, including the tongue, leads to declined swallowing function and dysphagia. Muscle mass and strength, and motor function in the oral region have not been examined together, and the relationship between generalised and oral sarcopenia remains unclear. Objective(s): The purpose of this study is to clarify the relationship between generalised sarcopenia and oral sarcopenia in the elderly in order to facilitate the establishment of a method for assessing oral sarcopenia. Methods: A total of 54 elderly persons participated in this study. We examined the skeletal muscle mass index (SMI), grip strength (GS) and walking speed (WS) as the index of generalised sarcopenia, and the cross‐sectional area of the geniohyoid muscle (CSG), tongue pressure (TP) and oral diadochokinesis (ODK) as the index of oral sarcopenia. Results: We found a moderate correlation between CSG and SMI, a weak correlation between GS and TP, and a moderate correlation between WS and ODK. CSG, TP and ODK were significantly smaller in the sarcopenia group than in the non‐sarcopenia group. By multiple regression analysis, SMI and TP were significantly associated with CSG. ODK, BMI and CSG were significantly associated with TP. WS and SMI were significantly associated with ODK. Conclusion: CSG, TP and ODK were confirmed as endpoints of oral sarcopenia. All endpoints of oral sarcopenia were influenced by those of generalised sarcopenia.